Influence of thickness of p-type diamond Hall sensors synthesized by HFCVD on their response sensitivity to magnetic field - Panyalert, Wasin; Siriwongrungson, Vilailuck; Suwanna, Prapakron; Titiroongruang, Wisut; Niemcharoen, Surasak (My University, 2018)
This article presents the study of the influence of thickness of p-type diamond Hall sensors, which were synthesized by HFCVD, on their response sensitivity to magnetic field. Boron was added in ethyl alcohol as the reactant to obtain p-type diamond film at B/C ratio of 10,000 ppm. The synthesis durations of 6, 12 and 36 hours at the substrate temperature of 750°C were selected to achieve the required diamond film thicknesses of 50, 100 and 150 µm, respectively. The synthetic diamond films were confirmed to be diamond using Raman spectroscopy and the cross sections were analyzed using SEM (Scanning Electron Microscopy). Then, simple p-type diamond Hall sensors were fabricated using four silver electrodes adhered on the diamond film. The ohmic of the electrodes were confirmed by the measurement of electrical properties of electrodes and magnetic field response at three different diamond thicknesses. The response sensitivity to magnetic field were 12, 9 and 6 µV/Gauss, respectively. When the thickness of the p-type diamond Hall sensor increased, the response sensitivity to magnetic field decreased.
Keywords: Diamond thin film; Hall Sensor; HFCVD; Model